Criança não é manga, não amadurece: conceito de maturação na teoria histórico-cultural - Asbahr, Flávia da Silva Ferreira [UNESP]; Nascimento, Carolina Picchetti (FapUNIFESP (SciELO), 2013)
The idea of "mature development" is based, frequently, on explanations of school failure: the student does not learn because he is immature and the school has to wait until he gets "mature". When one says that a child is not mature compared to the development already attained by an adult, one focuses only the quantitative differences between them and forgets that these new qualities of the adult did not arise by the maturation, but by the permanent appropriation process of the human culture. Thus, this idea of "maturity of development" expresses a deep biologization of the human being, reducing social and educational problems explanation to the biological apparatus of the individual. The purpose of this essay is to analyze the relationship between maturation and development, pointing out the limits of biologists’ explanations of human phenomena and the possibilities of explanation formulated by the historical-cultural theory to the organization of pedagogical work. This concept gives a new configuration to the role of maturation in the learning process and gives the school education a central role in the development of higher psychological functions. Thus, the school does not have to wait for the child’s maturation. Rather, it is its duty to create conditions for his/her maturation to become effective.

La idea de la "maduración del desarrollo" fundamenta, de modo bastante recurrente, las explicaciones sobre el fracaso escolar: el alumno no aprende porque es inmaduro, y le resta a la escuela esperar que él "madure". Cuando se dice que un niño no está maduro, en comparación al desarrollo ya alcanzado por un adulto, se focaliza apenas en las diferencias cuantitativas entre ellos y se olvida que esas nuevas cualidades del adulto no surgieron en él por la maduración, sino, por el permanente proceso de apropiación de la cultura humana. De esa forma, la referida idea de "maduración del desarrollo" expresa una profunda biologización del ser humano, reduciendo al aparato biológico del individuo la explicación de problemas sociales y educacionales. El objetivo de este ensayo es analizar las relaciones entre la maduración y el desarrollo, apuntando los límites de las explicaciones biologicistas de los fenómenos humanos y las posibilidades de la explicación elaborada por la teoría histórico cultural para la organización del trabajo pedagógico. Esa concepción reconfigura el papel de la maduración en el proceso de aprendizaje y le otorga a la educación escolar un lugar central en el desarrollo de las funciones psicológicas superiores. Así, no le cabe a la escuela esperar que el niño madure, al contrario, es su deber crear condiciones para que la madurez se efective.

A ideia da maturação do desenvolvimento fundamenta, de modo bastante recorrente, as explicações sobre o fracasso escolar: o aluno não aprende porque é imaturo, e resta à escola esperar que ele amadureça. Quando se diz que uma criança não está madura, em comparação ao desenvolvimento já alcançado por um adulto, foca-se apenas nas diferenças quantitativas entre eles e se esquece que essas novas qualidades do adulto não surgiram nele pela maturação, mas sim, pelo permanente processo de apropriação da cultura humana. Dessa forma, a referida ideia de maturação do desenvolvimento expressa uma profunda biologização do ser humano, reduzindo ao aparato biológico do indivíduo a explicação de problemas sociais e educacionais. O objetivo deste ensaio é analisar as relações entre a maturação e o desenvolvimento, apontando os limites das explicações biologicistas dos fenômenos humanos e as possibilidades da explicação elaborada pela teoria histórico-cultural para a organização do trabalho pedagógico. Essa concepção reconfigura o papel da maturação no processo de aprendizagem e confere à educação escolar um lugar central no desenvolvimento das funções psicológicas superiores. Assim, não cabe à escola esperar que a criança amadureça, ao contrário, é seu dever criar condições para que a maturação se efetive.
Children are not mangos, do not get ripe: concept of maturation in the historical-cultural theory
Un niño no es un mango, no madura: concepto de maduración en la teoría histórico cultura
Keywords: Human development; Learning; Childhood development; Cultural-historical theory; Desarrollo humano; Aprendizaje; Desarrollo infantil; Teoría histórico-cultural; Desenvolvimento humano; Aprendizagem; Desenvolvimento infantil; Teoria históricocultural